Characteristics of the shear mechanical properties and the influence mechanism of short basalt fiber reinforced polymer composite materials. (May 2019) - Chen, Jinxiang; Tuo, Wanyong; Wei, Peixing; Okabe, Yoji; Xu, Ming; Xu, Mengye
To increase the engineering applications of basalt fiber, the characteristics of the shear mechanical properties and the influence mechanisms of the fiber length ( Lf ) and volume fraction ( Vf ) for short basalt fiber reinforced epoxy resin polymer composites were investigated. The following results were obtained: (1) The first critical loads on all the shear load–displacement curves are close to the same value due to having the same interface bonding of the fiber–matrix; (2) the shear strength, deformation, and energy dissipation capacity all increase with increasing Vf ; however, when Lf is 6 or 9 mm, these increases are slower, whereas when Lf is 3 mm, these values increase at an approximately constant rate; and (3) the shear elastic modulus of the samples reaches its maximum value when Lf is 3 mm and Vf is 25%; however, it increases more quickly when Lf is 6 or 9 mm. The failure mode of the samples with the larger Lf values is mainly debonding between the fiber and matrix; when Vf is high, the fibers can easily bundle, which reduces the adhesion between the fibers and matrix. In addition, the main failure mode of the 3-mm-long fiber samples is fiber pull-out; when Vf is high, the short fibers that are not pulled out significantly increase the deformation ability.